(untitled) (Research, Society and Development, 2022)
Several studies have extensively discussed the effects of land use/cover changes on the hydrological regime. The application of hydrological models to describe this type of process, with greater flexibility, rigor, and lower cost, has become promising for decision-making. Therefore, the objective of this work was to evaluate the effect of land use/cover map uncertainties on the Una River basin hydrological regime. In this work, the SWAT model was adopted for hydrological simulation, comparing IBGE and MapBiomas land use/cover changes maps. Firstly, careful work was done on database building, containing geospatial files and tabular data on the climatic conditions of the study region for 55 years period (1961-2016). The results obtained showed the feasibility of hydrological studies using computational modeling. The generalities presented in the IBGE data makes it less sensitive (when compared to the MapBiomas data) to the influences of land use/cover changes in the hydrological regime.